Numerical studies on thermo-hydraulic performance of solar air heater with quarter circle roughness ribs - Yaregal Eneyew Bizuneh; Tazebew Dires Kassie; Atalay Enyew Bizuneh (Scientific Reports)
Abstract With their diverse range of applications, solar air heaters transform renewable solar energy into useful heat. The efficiency of solar air heater can be enhanced by exploring the effects of novel rib configurations. Despite the extensive work done so far on roughened solar air heaters, insufficient attention has been paid to the unique geometric features and potential advantages of quarter-circle ribs with respect to improving heat transfer efficiency. The fluid flow and heat transfer properties of a roughened solar air heater with quarter-circle-shaped ribs were examined in-depth using numerical analysis to improve the efficiency. The k–ε RNG turbulence model was used to conduct 2D steady-state numerical simulations, and the findings showed excellent agreement with the smooth duct and related literatures. The impact of rib spacing was explored by changing the rib relative pitch (p/e) from 6.67 to 13.3 for Reynolds range of 4000–20,000. The thermo-hydraulic performance factor was found to be 1.63. Additionally, it was shown that an increase in relative pitch (p/e) of 6.67 to 10 resulted in an increase in the Nusselt number for all Re values examined. At Re of 16,000, an enhancement of 2.42 times the Nu was made for p/e = 6.67. It was also noted that for all Re values taken into consideration, Nu falls with an increase in p/e from 10 to 13.3.